INDUSTRY 4.0: PRODUCTION FACTORIES TRANSFORMATION - I. V. Tarasov; N. A. Popov (Стратегические решения и риск-менеджмент, 2018)
The key stage of the company's transition to Industry 4.0. It is the Digital factory development stage. The first part of the article discusses in detail the components of digital factories, the expected effects of digitalization of production and related functions, as well as the transition from strategic initiatives to the operational level – the level of business processes that are transformed under the influence of new technologies. The second part of the article describes the methodology of case studies of Russian and foreign companies that are at the forefront of changes. The third part presents the cases of manufacturing companies that have achieved significant results in the field of digital transformation, in particular, Siemens, SIBUR and Novolipetsk metallurgical combine.